The Role of Mediation in Job Satisfaction in Relation to Work-Family Conflict and Organizational Commitment: A Study at PT. Ganesh International Filterindo - Sofyan, Mohamad; Iqbal, M. Ali (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the role of job satisfaction in the relationship between work-family conflict and Organizational Commitment in relation to turnover intention. This quantitative study involves 112 employees as the population, and sampling was conducted using full sampling. Data collection was done through a survey using a questionnaire as the survey instrument. Data analysis was carried out using Structural Equation Model - Partial Least Square (SEM-PLS). The results showed that work-family conflict has a positive and significant effect on turnover intention, Organizational Commitment has a negative and significant effect on turnover intention, job satisfaction has a positive and significant effect on turnover intention, work-family conflict has a positive and insignificant effect on job satisfaction, Organizational Commitment has a positive and significant effect on job satisfaction, job satisfaction does not mediate the relationship between work-family conflict and turnover intention, and job satisfaction can mediate the relationship between Organizational Commitment and turnover intention.